2005
DOI: 10.1074/jbc.m410508200
|View full text |Cite
|
Sign up to set email alerts
|

A Rac1/Phosphatidylinositol 3-Kinase/Akt3 Anti-apoptotic Pathway, Triggered by AlsinLF, the Product of the ALS2 Gene, Antagonizes Cu/Zn-superoxide Dismutase (SOD1) Mutant-induced Motoneuronal Cell Death

Abstract: AlsinLF, the product of the ALS2 gene, inhibits Cu/Znsuperoxide dismutase (SOD1) mutant-induced neurotoxicity via its Rho guanine nucleotide-exchanging factor domain. We here identified Rac1, a Rho family small GTPase, as a target for the Rho guanine nucleotide-exchanging factor activity of alsinLF. Rac1 associates with alsinLF. The amount of the GTP form of Rac1 is up-regulated by enforced overexpression of alsinLF. We further found not only that constitutively active Rac1 suppresses motoneuronal cell death i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
1
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 58 publications
3
86
1
1
Order By: Relevance
“…Based on previously reported in vitro data that ALS2 plays a protective role against mutant SOD1-mediated toxicity [7], we hypothesized that SOD1 G93A / ALS2 −/− mice would exhibit a shorter life span and display more severe motor neuron degeneration compared with SOD1 G93A /ALS2 +/+ mice. Surprisingly, we did not observe any obvious effects of the loss of ALS2 gene on motor neuron degeneration or survival of SOD1 G93A transgenic mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previously reported in vitro data that ALS2 plays a protective role against mutant SOD1-mediated toxicity [7], we hypothesized that SOD1 G93A / ALS2 −/− mice would exhibit a shorter life span and display more severe motor neuron degeneration compared with SOD1 G93A /ALS2 +/+ mice. Surprisingly, we did not observe any obvious effects of the loss of ALS2 gene on motor neuron degeneration or survival of SOD1 G93A transgenic mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we and others have generated ALS2 knockout (ALS2 −/− ) mice that failed to display any obvious motor neuron degeneration [1,4]. Since over-expression of ALS2 protects cells from SOD1-mediated cytotoxicity and loss of ALS2 predisposes neurons to paraquat-induced oxidative stress [1,7], ALS2 may serve as a risk factor for motor neuron disease. In this study, we examined whether the deficiency in the ALS2 gene affected the well-characterized motor neuron degeneration in SOD1 G93A transgenic mice [3].…”
Section: Introductionmentioning
confidence: 99%
“…It contains 3 putative GEF domains: an amino-terminal domain that displays homology to the Ran GEF RCC1; a central region containing Dbl and pleckstrin homology (DH/PH) domain that is present in GEFs for Rho, Rac and Cdc42; and a carboxyl-terminal vacuolar protein-sorting 9 (VPS9) domain that is found in GEFs for Rab5. Subsequent studies have indeed demonstrated that alsin acts in vitro as a GEF for Rab5 and Rac1 [43,63,80,81]. At present, it is very unclear how the Rac1 and Rab5 exchange activities of alsin influence motor neuron maintenance and survival and contribute to the disease of ALS.…”
Section: Alsinmentioning
confidence: 99%
“…With respect to alsin's role as a Rho family GEF, experiments have shown that alsin is an exchange factor for Rac1 [43,80,81]. Alsin specifically interacts with Rac1 and shows little, if any, association with Rac3, RhoA, or Cdc42.…”
Section: Alsinmentioning
confidence: 99%
“…8 We have independently shown that wild-type alsin suppresses mutant SOD1-induced neuronal cell death by activating a prosurvival pathway involving Rac1, PI3K and Akt3, and that FALS-linked mutations in the gene abolish the alsin function. 9,10 To further characterize the Akt-mediated prosurvival pathways that are linked to the ALS pathogenesis, we previously performed an yeast-two hybrid analysis and identified BTBD10 as an Akt3-binding protein. BTBD10 activates Akt by inhibiting PP2A-mediated Akt dephosphorylation and inactivation.…”
mentioning
confidence: 99%